GENETIC FEATURES OF STREPTOCOCCUS PNEUMONIAE AND ITS ROLE IN CAUSING MENINGITIS - Mahdi, Dunya Talib; Abed , Rana Jaafar (Antis-Publisher, 2024)
General background: Streptococcus pneumoniae is a major pathogen responsible for various severe diseases, including respiratory infections, bacteraemia, and otitis media, as well as bacterial meningitis. Specific background: Meningitis caused by S. pneumoniae is highly fatal, resulting from the bacteria crossing the blood-brain barrier into the subarachnoid space, triggering an immune response that can lead to central nervous system (CNS) damage. Knowledge gap: While vaccines like the pneumococcal conjugate and the 23-valent polysaccharide vaccines have reduced disease incidence, they remain insufficient against all serotypes, and antibiotic resistance is rising, underscoring the need for novel therapeutic approaches. Aims: This review aims to summarize the mechanisms by which S. pneumoniae causes meningitis, focusing on the interactions between CNS barriers, the host immune system, and the bacterial genetic features that facilitate infection. It also aims to highlight current limitations in treatment and the need for advanced genomic analyses for new therapeutic and diagnostic strategies. Results: The study outlines how S. pneumoniae colonizes the nasopharynx, evades host immune defenses, and crosses CNS barriers, leading to neuronal damage through inflammatory processes. Existing vaccines show efficacy but fail to cover all serotypes, and increasing antibiotic resistance exacerbates the challenge. Novelty: This review integrates knowledge of both bacterial genetics and host immune responses, emphasizing the interplay that drives CNS injury in meningitis. Furthermore, it stresses the critical need for refined genomic approaches to develop new therapeutic targets. Implications: Understanding the pathogenesis of S. pneumoniae meningitis and advancing vaccine development are crucial for reducing mortality and improving clinical outcomes in both children and adults globally.